(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In clause it is considered a problem offormalion of creative abilities of pupils at lessons of technology by ways of introduction project activities. The problem offormation of creative abilities of pupils at lessons of techmolog is shown. The received results enable to assert (approve), that it is important to introduce design ac iviny in school practice.